The effect of probiotics and casein supplementation on aerobic capacity parameters of male soccer players - Babak Imanian; Mohammad Hemmatinafar; Farhad Daryanoosh; Negar Koureshfard; Reza Sadeghi; Alireza Niknam; Rasoul Rezaei; Ali Qashqaei (Journal of the International Society of Sports Nutrition, 2024)
Background In the realm of sports science, nutrition is a well-established pillar for athletes’ training, performance, and post-workout recovery. However, the role of gut microbiota, often overlooked, is a novel and intriguing aspect that can significantly impact athletic performance. With this in mind, our study ventures into uncharted territory, investigating the effect of probiotic and casein supplementation on the aerobic capacity of male soccer players.Method A double-blinded and placebo-controlled study was conducted with 44 male soccer players (Age: 22.81 ± 2.76 yr, Height: 177.90 ± 6.75 cm, Weight: 67.42 ± 8.44 kg). The participants were subjected to the Bruce test in the beginning; then, they were randomly divided into four groups, each consisting of 11 people: probiotics (PRO), casein (CAS), probiotics with casein (PRO+CAS), and placebo (PLA). PRO group was given one probiotic capsule (containing strains of Lactiplantibacillus plantarum BP06, Lacticaseibacillus casei BP07, Lactobacillus acidophilus BA05, Lactobacillus delbrueckii BD08 bulgaricus, Bifidobacterium infantis BI04, Bifidobacterium longum BL03, Bifidobacterium breve BB02 and Streptococcus salivarius thermophilus BT01, with a total dose of 4.5 × 1011 CFU) during dinner, while the CAS group consumed 20 grams of casein powder 45 minutes before bed. The PRO+CAS group was given one probiotic capsule during dinner and 20 grams of casein powder 45 minutes before bed. The participants in the PLA group were given one red capsule (containing 5 grams of starch) during dinner. All participants were instructed to take the supplements only on training days, three times a week for four weeks. The maximal oxygen consumption (VO2max), Ventilatory Threshold (VT), Time-to-exhaustion (TTE), Respiratory Compensation Point (RCP), Isocapnic area Time (Time-IC), Isocapnic area oxygen consumption (VO2-IC), and Hypocapnic Hyperventilation area Time (Time-HHV), after the Bruce test were Measured. All data were analyzed using SPSS Windows software, mixed repeated measure ANOVA, and Bonferroni post hoc test at p < 0.05 level.Results The current study’s findings illustrated that, after the intervention, TTE (p = 0.01) and RCP (p = 0.01) were significantly improved in PRO+CAS compared to the PLA group. No significant difference was observed between PRO and PLA (p = 0.52), PRO and CAS (p = 0.999), PRO and PRO+CAS (p = 0.9), CAS and PLA (p = 0.65), CAS and PRO+CAS (p = 0.73) in TTE. In addition, no significant difference was observed between PRO and CAS (p = 0.999), PRO and PLA (p = 0.40), PRO and PRO+CAS (p = 0.999), CAS and PLA (p = 0.263), CAS and PRO+CAS (p = 0.999) in RCP. Time-HHV was significantly higher in PRO+CAS (p = 0.000) and CAS (p = 0.047) compared to the PLA group. However, no significant difference was observed in the Time-HHV between PRO and CAS (p = 0.999), PRO and PRO+CAS (p = 0.25), PRO and PLA (p = 0.12), and CAS and PRO+CAS (p = 0.57). Additionally, all the groups had no significant differences in VO2max, VT1, VO2-IC and Time-IC.Conclusion The findings showed that consuming probiotics and casein could relatively improve the aerobic capacity of male soccer players. Nevertheless, simultaneous consumption of probiotics and casein had a more pronounced effect on aerobic capacity indicators, especially TTE and Time-HHV.